Measuring and achieving moderate-scale operation of new agricultural business entities in hilly and mountainous areas: an empirical study on citrus, pepper, and grain farming in Chongqing's Jiangjin Modern Agricultural Park, China - Zhang, ShiChao; Zhang, Xiang; Zhang, XuanYun; Lu, ZhangYe (Frontiers in Sustainable Food Systems, 2025)
Moderate-scale agricultural operations are central to improving the quality and efficiency of modern regional agriculture and advancing agricultural modernization. It is particularly crucial for addressing persistent challenges, such as land fragmentation, low mechanization efficiency, and population aging, in hilly and mountainous areas. This study estimates the moderate operating scale for new agricultural business entities (NABEs) across various crop types and investigates strategies to achieve such scale. Drawing on data from 277 NABEs engaged in citrus, pepper, and grain farming in Chongqing's Jiangjin Modern Agricultural Park, we employ a translog production function to determine moderate-scale thresholds and a structural equation model (SEM) to examine both internal and external pathways toward achieving these thresholds. The findings show that the average moderate scale per labor for citrus, pepper, and grain farming is 2.55 hm2, 2.67 hm2, and 1.72 hm2, respectively. Among the three, 13.33% of pepper-farming NABEs (16 households) reach the moderate scale, which has the highest share, while only 2.04% of grain-farming NABEs (one household) do so, representing the lowest share. Most NABEs operate either below or above the moderate scale. For NABEs exceeding the moderate scale, internal pathways are key (improving effective labor, adjusting business models, and investing in fixed assets and liquidity). For those below, external pathways matter (expanding their farming scale under suitable conditions). Specifically, citrus-farming NABEs should prioritize villages with higher per capita arable land and improved land conditions, while pepper- and grain-farming NABEs should focus on areas with higher per capita income and proximity to residential settlements. This study offers practical guidance for NABEs of different crops in hilly and mountainous areas to achieve moderate-scale operations through appropriate pathways, contributing to sustainable and efficient agricultural development in these regions.